Effects of carbon disulphide on the liver of rats - Bond, E. J. (1969)
Bond, E. J., Butler, W. H., de Matteis, F., and Barnes, J. M. (1968).Brit. J. industr. Med.,26, 335-337. Effects of carbon disulphide on the liver of rats. Normal rats surviving a single oral dose of carbon disulphide (CS(2)) show liver enlargement and depression of drug-metabolizing enzymes but no liver necrosis. If the drug-metabolizing enzymes are stimulated by phenobarbitone before exposure to CS(2,) the LD(50) does not change but liver necrosis is produced.